Crystal Structure and Stereochemistry Study of 2-Substituted Benzoxazole Derivatives. (13th May 2014) - Mabied, Ahmed F.; Shalaby, Elsayed M.; Zayed, Hamdia A.; El-Kholy, Esmat; Farag, Ibrahim S. A.; Ahmed, Naima A.
Abstract : The structure of 2-[(4-chlorophenylazo) cyanomethyl] benzoxazole, C15 H9 ClN4 O (I), has triclinic (P 1 ̅ ) symmetry. The structure displays N – H ⋯ N hydrogen bonding. The structure of 2-[(arylidene) cyanomethyl] benzoxazoles, C17 H10 N2 O3 (II), has triclinic (P 1 ̅ ) symmetry. The structure displays C – H ⋯ N, C – H ⋯ C hydrogen bonding. In (I), the chlorophenyl and benzoxazole groups adopt a trans configuration with respect to the central cyanomethyle hydrazone moiety. Compound (II) crystallized with two molecules in the asymmetric unit shows cisoid conformation between cyano group and benzoxazole nitrogen, contrary to (I). In (II) the benzodioxole has an envelope conformation (the C17 atom is the flap atom). The molecular geometry obtained using molecular mechanics (MM) calculations has been discussed along with the results of single crystal analysis.